A sociological examination of the contemporary animal advocacy movement: Organisations, rationality and veganism - Pendergrast, Nicholas Preston (Curtin University, 2014)
This thesis analyses the animal advocacy movement, examining its ideological foundations and other factors that influence animal advocacy organisations. There is a particular emphasis on the differences between animal rights and animal welfare, as well as the emergence of veganism. Animal advocacy campaigns are analysed from a sociological perspective, drawing on theories related to social movements and organisations. The central research question is: how are animal advocacy campaigns consistent with different forms of rationality and organisational forms?